School performance is impaired in children with both simple and complex congenital heart disease - Omann, Camilla; Kristensen, Rasmus; Tabor, Ann; Gaynor, J. William; Hjortdal, Vibeke E.; Nyboe, Camilla (Frontiers in Pediatrics, 2023)
Background: We do not know if children born with a simple or uncorrected congenital heart disease (CHD) have school performance issues and an increased need for special education compared to healthy peers. With this study we examine the school performance and the need for special education in children with both simple and complex CHD. Further, we evaluate if exposure to preeclampsia or smoking affects the need for special education. Methods: In this nation-wide population based registry study, we included all Danish children with CHD born 1994-2012. In addition ten age and gender matched control per CHD child were included. Non-singletons and children born with a syndrome were excluded. Exposure was defined as having a CHD and the outcome was defined as needing special education service in the Danish primary and lower secondary school. Results: The population consisted of 7,559 CHD children and 77,046 non-CHD children (controls). CHD children had a higher need for special education compared to non-CHD children, OR: 2.14 (95%CI: 2.00;2.28), p < 0.001. The odds ratio was also increased when comparing children with a minor CHD to non-CHD children, OR: 1.99 (95%CI: 1.86;2.14), p<0.001. CHD children exposed to preeclampsia or smoking had a higher risk of receiving special education compared to unexposed CHD children. Conclusion: We find that school performance is impaired in children born with CHD. This applies to both simple and complex CHD. If a child with CHD was exposed to preeclampsia or maternal smoking this further increased the need for special education.